Alcohol consumption, masculinity, and alcohol-related violence and anti-social behaviour in sportspeople. Issue 4 (April 2018) - O'Brien, Kerry S.; Forrest, Walter; Greenlees, Iain; Rhind, Daniel; Jowett, Sophia; Pinsky, Ilana; Espelt, Albert; Bosque-Prous, Marina; Sonderlund, Anders Larrabee; Vergani, Matteo; Iqbal, Muhammad
Abstract: Objectives: There is no research examining alcohol-related aggression and anti-social behaviour in UK or European sportspeople (athletes), and no research has examined relationships between masculinity, alcohol consumption, and alcohol-related aggression and antisocial behaviour in sportspeople (athletes). This study addresses this gap. Design: Cross-sectional. Methods: A sample ( N = 2048; women = 892, 44%) of in season sportspeople enrolled at UK universities (response 83%), completed measures of masculinity, alcohol consumption, within-sport (on-field) violence, and having been the perpetrator and/or victim of alcohol-related violent/aggressive and antisocial behaviour (e.g., hit/assaulted, vandalism, sexual assault). Logistic regressions examined predictors of alcohol-related violence/aggression and anti-social behaviours. Results: Significant bivariate relationships between masculinity, within-sport violence, alcohol consumption, and alcohol-related aggression and anti-social behaviour were found for both men and women ( p 's < .001). Logistic regression adjusting for all variables showed that higher levels of masculinity and alcohol consumption in men and women were related to an increased odds of having conducted an aggressive, violent and/or anti-social act in the past 12 months when intoxicated. Odds ratios were largest for relationships between masculinity, alcohol consumption, within-sport violence, and interpersonal violence/aggression ( p 's < .001). A similar pattern of results was found for having been the victim of aggression and anti-social behaviour. Conclusions: Alcohol-related aggression and anti-social behaviour appear to be problematic in UK university sportspeople, and is related to masculinity and excessive drinking. Interventions that reduce excessive alcohol consumption, masculine norms and associated within-sport violence, could be effective in reducing alcohol-related aggression and antisocial behaviour in UK sportspeople.